1998
DOI: 10.1103/physrevlett.80.704
|View full text |Cite
|
Sign up to set email alerts
|

Self-Similar Capillary Pinchoff of an Inviscid Fluid

Abstract: We study how an axisymmetric drop of inviscid fluid breaks under the action of surface tension. The evolution of various initial shapes is calculated numerically using a boundary-element method, and finite-time breakage is observed in detail. The pinchoff region is shown to have lengths scaling as t 2͞3 , where t is the time remaining until pinchoff, and is found to adopt a unique shape with two cones of angles 18.1 ± and 112.8 ± , independent of the initial conditions. The velocity potential in the intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
262
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(293 citation statements)
references
References 8 publications
28
262
3
Order By: Relevance
“…This therefore sets bubble detachment apart from all other breakup situations studied so far where one or both fluids are viscous, or where two inviscid fluids differ little in density, as well as from the inverse case of water in air. In those cases, the breakup is driven by surface tension and α h ≥ 2/3 [3,4,5,6,7,8,9,10,11,12,20]. Here we observe the consequences of a different driving mechanism on the breakup dynamics.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…This therefore sets bubble detachment apart from all other breakup situations studied so far where one or both fluids are viscous, or where two inviscid fluids differ little in density, as well as from the inverse case of water in air. In those cases, the breakup is driven by surface tension and α h ≥ 2/3 [3,4,5,6,7,8,9,10,11,12,20]. Here we observe the consequences of a different driving mechanism on the breakup dynamics.…”
mentioning
confidence: 75%
“…Each symmetry in nature implies an underlying conservation law, so that the symmetries of the singularity associated with pinch-off naturally have important consequences for its dynamics. It was previously believed [1,2,3,4,5,6,7,8,9,10,11,12] that the pinching neck of any drop or bubble would become cylindrically (i.e. azimuthally) symmetric in the course of pinch-off.…”
mentioning
confidence: 99%
“…In particular, for inviscid irrotational flows it has been shown that the simplified one-dimensional Euler equations exhibit a singularity before the point of breakup is reached 48 . Numerical simulations 49,50 show that in fact the free-surface of the droplet close to the singularity overturns.…”
Section: A Model For Inertio-elastic Pinchingmentioning
confidence: 99%
“…If this cannot occur quickly enough, then the surface tension forces will act to breakup elongated structures through the Rayleigh-Plateau instability. At the final moments of progeny drop pinch-off, the charge density remains finite and the dynamics are governed by the known universal solution for inviscid capillary pinchoff [26]. Fig.…”
mentioning
confidence: 99%